Japanese Language Intonation By Japanese Language Education Students - G.Y Sompotan, Amelia; Pandi, Helena; F. Lensun, Sherly (KnE Social Sciences, 2024)
When learning Japanese we will come across sentences that are the same but have different meanings. Because of the similarity of the sentences, many students who study Japanese often make mistakes in pronouncing the sentence and also in understanding the true meaning of it. In written language, the meaning of sentences in Japanese can be distinguished by punctuation. For example, an interrogative sentence can be distinguished by looking at the ka(か) particle behind the sentence, then a command sentence, and so on can be identified by looking at the predicate. However, in conversations, especially informal conversations, it becomes vague, for example, the loss of the ka(か) particle in interrogative sentences and so on. This can be understood by the interlocutor when we use the right intonation. In learning Japanese, less is taught about intonation differences, and there are many misunderstandings when communicating with Japanese people. Therefore, the researcher did study about the difference in meaning caused by intonation in the same sentence. This study aimed to identify intonation in sentences produced by students of the Japanese language study program. This research was carried out using exploratory qualitative research methods and data were collected using in-depth interviews. The data collected in the form of spoken sentences spoken by Japanese language study program students who are also native Japanese were classified, analyzed, and then described in writing. Interview transcripts were analyzed using thematic content analysis using a Speech Analyzer (SA) as a tool for recording, transcribing, and analyzing speech sounds. Linguists and ethnomusicologists can use SA to investigate, imitate, and explain the acoustic sounds of human language. The main respondents were students of the UNIMA Japanese Language Education Study Program. The number of respondents targeted was 30 people with a duration of 15 min of interviews. The selection of respondents were 5th-semester students who had studied Japanese for approximately 2 years and met the criteria of having studied bunpo and dokkai. Other data sources are in the form of linguistic theory and language comparison Keywords: language, intonation, Japanese, , education, students